Taxation of foreign profits with heterogeneous multinational firms - Johannes Becker (Center for Economic Studies and ifo Institute (CESifo), 2009)
Recent empirical studies find that foreign direct investment (FDI) by a multinational firm is not associated with a reduction of the firm’s domestic activities. As it is often argued, this finding may imply that a country should not tax the firm’s foreign profit income since this reduces foreign investment without benefitting the domestic economy. The paper analyzes this argument using a model with heterogeneous multinational firms which serve a foreign market through exports or FDI. If a firm switches from exporting to FDI, domestic activity and tax payments may decrease, stay constant or even rise due to intra-firm trade. It turns out that, in all three cases, the optimal tax system implies full taxation after deduction of foreign tax payments. If the country accounts for the effects of its policy on the foreign price level, the case for taxing foreign income becomes even stronger. From a global point of view, the nationally optimal tax rate on repatriated foreign profits is inefficiently high. In contrast to the standard literature, the globally optimal tax system requires a lower tax rate than under the tax credit system which, under certain circumstances, may imply exempting foreign income from tax.
Keywords: H25; F23; 330; corporate taxation; foreign profits; multinational firms